Molecular dynamics of the human RhD and RhAG blood group proteins - Floch, Aline; Galochkina, Tatiana; Pirenne, France; Tournamille, Christophe; de Brevern, Alexandre G. (Frontiers in Chemistry, 2024)
Introduction: Blood group antigens of the RH system (formerly known as “Rhesus”) play an important role in transfusion medicine because of the severe haemolytic consequences of antibodies to these antigens. No crystal structure is available for RhD proteins with its partner RhAG, and the precise stoichiometry of the trimer complex remains unknown. Methods: To analyse their structural properties, the trimers formed by RhD and/or RhAG subunits were generated by protein modelling and molecular dynamics simulations were performed. Results: No major differences in structural behaviour were found between trimers of different compositions. The conformation of the subunits is relatively constant during molecular dynamics simulations, except for three large disordered loops. Discussion: This work makes it possible to propose a reasonable stoichiometry and demonstrates the potential of studying the structural behaviour of these proteins to investigate the hundreds of genetic variants relevant to transfusion medicine.